“Imprisoned Photographs”: The Looted Archive of Photo Rissas (Rassas)—Ibrahim and Chalil (Khalil) Rissas - Sela, Rona (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2018)
This essay is the first dedicated solely to the work and archive of Ibrahim and Chalil (Khalil) Rissas (Rassas). Ibrahim was one of the pioneers of Palestinian photography in Jerusalem in the early twentieth century and Chalil, his son, was one of the first Palestinian photojournalists in the 1940s. Rissas’ images were looted and seized by Israeli officer from the photographers’ studio, from the body of a soldier or “slain Arab,” or “rescued” from a burning shop. Those photographs that had been looted from the studio, were the first collection I found in the Israeli military archives. In this essay I chart and analyze the way Rissas’ images were looted on several occasions and the moral, sociological, and political consequences of these acts—for instance how the looted object becomes a symbol of triumph or acts as a vehicle to dehumanize the enemy. The essay is also the first to focus on the phenomenon of pillage by individuals who transfer the looted cultural assets to colonial official archives where they are ruled by the colonial administration. It thus reflects not only the responsibility of states in the process of “knowledge production” and on their role in distorting the past and rewriting history by various bureaucratic, linguistic, and legal means, but also on the role of citizens in these destructive processes.